Functional polymorphisms within the inflammatory pathway regulate expression of extracellular matrix components in a genetic risk dependent model for anterior cruciate ligament injuries. Issue 11 (November 2019) - Suijkerbuijk, Mathijs A.M.; Ponzetti, Marco; Rahim, Masouda; Posthumus, Michael; Häger, Charlotte K.; Stattin, Evalena; Nilsson, Kjell G.; Teti, Anna; Meuffels, Duncan E.; van der Eerden, Bram J.C.; Collins, Malcolm; September, Alison V.
Abstract: Objectives: To investigate the functional effect of genetic polymorphisms of the inflammatory pathway on structural extracellular matrix components (ECM) and the susceptibility to an anterior cruciate ligament (ACL) injury. Design: Laboratory study, case–control study. Methods: Eight healthy participants were genotyped for interleukin (IL) 1B rs16944 C > T and IL6 rs1800795 G > C and classified into genetic risk profile groups. Differences in type I collagen ( COL1A1 ), type V collagen ( COL5A1 ), biglycan ( BGN ) and decorin ( DCN ) gene expression were measured in fibroblasts either unstimulated or following IL-1β, IL-6 or tumor necrosis factor (TNF)-α treatment. Moreover, a genetic association study was conducted in: (i) a Swedish cohort comprised of 116 asymptomatic controls (CON) and 79 ACL ruptures and (ii) a South African cohort of 100 CONs and 98 ACLs. Participants were genotyped for COL5A1 rs12722 C > T, IL1B rs16944 C > T, IL6 rs1800795 G > C and IL6R rs2228145 G > C. Results: IL1B high-risk fibroblasts had decreased BGN ( p = 0.020) and COL5A1 ( p = 0.012) levels after IL-1β stimulation and expressed less COL5A1 ( p = 0.042) following TNF-α treatment. Similarly, unstimulated IL6 high-risk fibroblasts had lower COL5A1 ( p = 0.012) levels than IL6 low-risk fibroblasts. In the genetic association study, the COL5A1-IL1B-IL6 T–C–G ( p = 0.034, Haplo-score 2.1) and the COL5A1-IL1B-IL6R T–C–A ( p = 0.044, Haplo-score: 2.0) combinations were associated with an increased susceptibility to ACL injury in the Swedish cohort when only male participants were evaluated. Conclusions: This study shows that polymorphisms within genes of the inflammatory pathway modulate the expression of structural and fibril-associated ECM components in a genetic risk depended manner, contributing to an increased susceptibility to ACL injuries.